Enabling hydrate-based methane storage under mild operating conditions by periodic mesoporous organosilica nanotubes - Beckwée, Emile Jules; Watson, Geert; Houlleberghs, Maarten; Arenas Esteban, Daniel; Bals, Sara; Van Der Voort, Pascal; Breynaert, Eric; Martens, Johan; Baron, Gino V.; Denayer, Joeri F.M. (Heliyon, 2023)
Biomethane is a renewable natural gas substitute produced from biogas. Storage of this sustainable energy vector in confined clathrate hydrates, encapsulated in the pores of a host material, is a highly promising avenue to improve storage capacity and energy efficiency. Herein, a new type of periodic mesoporous organosilica (PMO) nanotubes, referred to as hollow ring PMO (HR-PMO), capable of promoting methane clathrate hydrate formation under mild working conditions (273 K, 3.5 MPa) and at high water loading (5.1 g water/g HR-PMO) is reported. Gravimetric uptake measurements reveal a steep single-stepped isotherm and a noticeably high methane storage capacity (0.55 g methane/g HR-PMO; 0.11 g methane/g water at 3.5 MPa). The large working capacity throughout consecutive pressure-induced clathrate hydrate formation-dissociation cycles demonstrates the material’s excellent recyclability (97% preservation of capacity). Supported by ex situ cryo-electron tomography and x-ray diffraction, HR-PMO nanotubes are hypothesized to promote clathrate hydrate nucleation and growth by distribution and confinement of water in the mesopores of their outer wall, along the central channels of the nanotubes and on the external nanotube surface. These findings showcase the potential for application of organosilica materials with hierarchical and interconnected pore systems for pressure-based storage of biomethane in confined clathrate hydrates. [Display omitted]